Dentinal carious lesion in three dimensions - F. S. L. WONG, N. S. WILLMOTT & G. R. DAVIS (Paediatric Dentistry, 2006)
The aim of this study was to show the morphology of the carious lesion in dentine in three dimensions (3D).